The Morlachs of Dalmatia during the 15th and 16th century. A Venetian perspective - Caciur, Dana (Balcanica Posnaniensia. Acta et studia, 2021)
The article aims to present the main features of the character of the Morlachs living in the Venetian Dalmatia during the Fifteenth and Sixteenth centuries. The research approach focuses on Venetian sources, published and unpublished, therefore the portray of the Morlachs built up in this study is an external one. According to it the Morlachs appear as nomadic people who develop occasional or permanent activities in the Venetian hinterland of Dalmatia. Either they are presented by the sources as shepherds, soldiers, immigrants, merchants, criminals or in many other situations, the Morlachs became agents of coexistence in the permeable area of the Venetian-Ottoman border. This is why, one of the ideas promoted by this study is that the survival of the Morlach`s presence in Dalmatia was assured by the political instability.